Strategi Pengembangan Budaya Religius di Madrasah - Edi Mulyadi (Institut Agama Islam Negeri Purwokerto, 2018)
As an educational institution characterized by Islam, madrasah must be able to fulfill the community needs on the education of their children in order to avoid the negative effects of technological developments. This matter will be one of the attractions for the community to send their children to madrasah. One of the efforts to realize it is by developing a religious culture among madrasahs, ie continuously practicing religious habits, so that religious values can be internalized and practiced in everyday life. Among the strategies of religious culture development that can be done is through power strategy, persuasive strategy, and normative re-educative. The first strategy was developed through a command approach and a ban or reward and punishment. The second and third strategies are developed through habituation, exemplary, and persuasive approach or inviting to its citizens in a subtle way. In practice, the implementation of the development of religious culture requires the support and active role of various implementers and stakeholders such as teachers, students, parents, communities and governments.